Kalamasutta and Rumor Spreading Tactics - Yussayotha, Amnuay (Journal of Social Sciences and Humanities Research in Asia, 2021)
The “Kalamasutta” is a sutra that the Lord Buddha presented to the Kalama people in order to teach them not to be credulous. This study only discusses the third belief, which is known in Pali as “Ma Itikirai”, which means “not to be led by rumor”. Rumor refers to unconfirmedinformation that is spread for a certain reason. In the Buddha’s period, monks of different sects exploited rumors as a ruse to harm Buddhism. Monks of various sects exploited it as a ruse to create misinformation in order to harm Buddhism. The Buddha employed advanced strategies to counter with many different types of rumors that gradually faded away, as well as increase faith in Buddhism. People nowadays utilize fake news for many reasons, and discrediting others. The propagation of most rumors aims at political and public figures destabilization. To stop rumors, the persons need to prove that the rumors are not true and take action to reclaim their trustworthiness. People in the society must also be ‘well equipped with intellectual weapons’ so that they will no longer be trapped in a rumor. including making profits, propagandizing, creating news,